2018
DOI: 10.1186/s12917-018-1522-0
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of rectal levetiracetam as add-on treatment in dogs affected by cluster seizures or status epilepticus

Abstract: BackgroundLevetiracetam can be used for seizure control alone or in combination with other antiepileptic medications. A previous study achieved the minimum targeted serum drug concentration after rectal administration of levetiracetam in healthy dogs. The purpose of the present study was to determine the pharmacokinetics of rectal LEV in dogs presented for cluster seizures or status epilepticus and potentially in treatment with other anti-epileptic drugs. Furthermore, preliminary information on response to thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 25 publications
(20 reference statements)
0
13
0
Order By: Relevance
“…The LEV suspension employed was created and administered as previously reported . The dogs were monitored for additional seizures for the first 24 hours after admission and until discharge.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The LEV suspension employed was created and administered as previously reported . The dogs were monitored for additional seizures for the first 24 hours after admission and until discharge.…”
Section: Methodsmentioning
confidence: 99%
“…The pharmacokinetics of LEV after rectal administration in both healthy and epileptic dogs recently has been investigated. These studies indicated that administration of 40 mg/kg per rectum achieved the minimum target concentration of 5 μg/mL 10 and 30 minutes after the administration in healthy and affected dogs, respectively …”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations